2002
DOI: 10.1517/14728222.6.4.491
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of transcription factor interactions in myeloid stem cell development and leukaemia

Abstract: Recent results indicate that interactions of transcription factors with other nuclear proteins play an important role in stem cell development, lineage commitment and differentiation in the haematopoietic system, and the pathogenesis of myeloid leukaemias. High-throughput proteomics by mass spectrometric analysis of gel-separated proteins can identify multi-protein complexes and changes in the expression of multiple proteins simultaneously. This review describes an application of proteomic methods (2D gel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…65 The use of approaches of functional genomics and proteomics has allowed the discovery of new proteins involved in the origin of the neoplasia and their participation in the development of the disease. Emerging studies have identified the changes in the proteasome associated with the action of Bcr-Abl tyrosine kinases in chronic myeloid leukemia, 66 protein targets of transcription factors involved in myeloid stem cell development and leukemia, 67 or new protein …”
Section: Proteomic Approaches To the Altered Expression Of Tf And Vegmentioning
confidence: 99%
“…65 The use of approaches of functional genomics and proteomics has allowed the discovery of new proteins involved in the origin of the neoplasia and their participation in the development of the disease. Emerging studies have identified the changes in the proteasome associated with the action of Bcr-Abl tyrosine kinases in chronic myeloid leukemia, 66 protein targets of transcription factors involved in myeloid stem cell development and leukemia, 67 or new protein …”
Section: Proteomic Approaches To the Altered Expression Of Tf And Vegmentioning
confidence: 99%
“…Potential antagonistic protein interactions leading to a block in C/EBPa function in AML have been well implicated in recent findings (Pabst et al, 2001a;Vangala et al, 2003;Zheng et al, 2004). Interestingly, C/EBPa also functions via direct proteinprotein interactions in normal stem cell development (Behre et al, 2002a;D'Alo et al, 2003;Muller et al, 2004); PU.1 and c-Jun inactivation (Rangatia et al, 2002;Reddy et al, 2002), E2F repression (Porse et al, 2001), and cdk2 and cdk4 inhibition (Wang et al, 2001) by C/EBPa are all accompanied by direct protein-protein interactions. Moreover, different protein partners of C/EBPa in young and old mice livers itself demonstrate the importance of protein-protein interactions during ageing (Iakova et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Most of the proteomics experiments with time frames longer than 24 h explore the long-term transformations of cells [95,96]. These effects may be related to cells of a selected type, e.g., exploring the differentiation of cells, or to cells in a context of multicellular organisms, e.g., the study of cells in a developing body.…”
Section: Dynamics Of Proteomesmentioning
confidence: 99%
“…These effects may be related to cells of a selected type, e.g., exploring the differentiation of cells, or to cells in a context of multicellular organisms, e.g., the study of cells in a developing body. This includes the profiling of various tissues and different cell lines that originate from the same tissue [95,96]. Thus, longer time frames in proteomics studies are associated with the larger complexity of the studied system (Fig.…”
Section: Dynamics Of Proteomesmentioning
confidence: 99%